The Effect of Chloride and Sulfate Ions on the Adsorption of Cd2+ on Clay and Sandy Loam Egyptian Soils - Mohamed E. EL-Hefnawy; Elmetwaly M. Selim; Faiz F. Assaad; Ali I. Ismail (The Scientific World Journal)
Adsorption of Cd2+ on two types of Egyptian soils: clay (alluvial) and sandy loam (calcareous), was studied. Effect of changing the matrix electrolyte type and concentration was used to mimic the natural soil salts. Kinetics and thermodynamic parameters of the adsorption were calculated at two different electrolyte concentrations: 0.05 N and 0.15 N. The adsorption was described by Langmuir and Freundlich isotherms. Results showed that lower concentration of the NaCl or Na2SO4 electrolytes (0.05 N) had higher adsorption capacity. Also, the maximum adsorption of cadmium when using sulfate counter ion is about two to three times higher than that when using chloride (544 μg/g for alluvial soil and 170 μg/g for calcareous soil when using 0.05 N). Using NaCl as matrix electrolyte, Freundlich isotherms showed bi-linear fits that probably mean a two energy level adsorption. This might be explained by either the competition of Cd2+ with Na+ or its complexation with Cl−.